Modification of the thermodynamic variability closure in the Met Office Unified Model prognostic cloud scheme. (4th December 2020) - Morcrette, Cyril J.
Abstract: In the Met Office Unified Model prognostic cloud scheme (PC2), thermodynamic variability is represented by considering two distributions, based on the properties of the clear and cloudy portions of the grid‐box. To calculate a cloud fraction increment, the equation set needs to be closed. The closure assumption determines how these two distributions are blended together at the saturation boundary. The current closure is reviewed. In the limit of vanishing liquid condensate, this can lead to very tall but narrow probability distribution functions (PDFs). At present, the two parts of the PDF are weighted based on the area under their curves. As a result, these very tall PDFs are allowed to contribute significantly, since their area is finite. This closure is shown to sometimes lead to unphysically large cloud fraction changes. However, they are prevented from affecting the model evolution by being overwritten if their magnitude is unrealistically large. A new blending closure is proposed. This weighs the two PDFs based on their widths. The contribution of very tall, but narrow, PDFs is hence drastically reduced. While this removes the undesirable need for overwriting unrealistic increments, it is shown that overall model performance did not improve or worsen. Abstract : The height and width of the probability distribution functions (PDF) associated with two points where the current closure is leading to cloud fraction changes with a magnitude of more than one. The dry PDFs (brown) are shown on the left and the moist ones (cyan) on the right. Note the logarithmic scale for both the height and width. The horizontal lines show the blended value using the original (solid red) and new (dashed green) closure formulations.